Service Quality as The Critical Dimension of Learning Management System Quality in Education Service Provider: Evidence From Indonesia - Dwi Putri Ayuningtyas Ayuningtyas; Nur Budi Mulyono Mulyono (Economics and Business Journal (ECBIS), 2026)
The issue of digitalization of education has led to the increased dependency on Information Systems (IS), especially Learning Management Systems (LMS), to provide continuity of learning after the COVID-19 pandemic situation. At Edulab, as a large learning service provider in Indonesia, LMS works as a central of learning provision, evaluation, communication, and academic tracking. Despite the strategic role, there are still frequent problems like unreliable access, incomplete evaluation, flawed data, and deteriorated performance when the system is at its peak usage, and it interferes with the learning processes and lowers the level of user confidence. This paper discusses the effect of LMS quality on service delivery, satisfaction among users and effectiveness of the entire platform at the institution. It is being analyzed in terms of the DeLone and McLean Information System Success Model, which is being supplemented by the Technology-Organization-Environment (TOE) framework. The mixed method was used, which integrated a survey of 1,081 users of the LMS who were estimated through Structural Equation Modeling (SEM) and a semi-structured interview with key stakeholders of the management. The results suggest that system, information, and service quality are very powerful predictors of user satisfaction with service quality coming out as the most significant factor in LMS effectiveness in service-oriented institutions of learning.